Cardiovascular Risk Factors in Pathology - Abukabda, Alaeddin; Suciu, Maria; Andor, Minodora (IntechOpen, 2021)
This book provides a broad overview of the molecular mechanisms associated with relevant and significant cardiovascular conditions that continue to plague humanity. It also discusses potential and promising therapeutic avenues targeted at addressing these conditions. The overarching goal of this multifaceted work is to entice future and current members of the scientific community to direct their endeavors towards improving our current knowledge of cardiovascular disease conditions and curb their impact on our everyday lives.